Clinical characteristics and prognosis of non‐B non‐C hepatocellular carcinoma patients with modest alcohol consumption. Issue 5 (9th September 2015) - Urata, Yohei; Yamasaki, Takahiro; Saeki, Issei; Iwai, Shuji; Kitahara, Masaaki; Sawai, Yoshiyuki; Tanaka, Kazunari; Aoki, Tomoko; Iwadou, Shouta; Fujita, Naoki; Nakayama, Yasuhiro; Maeshiro, Tatsuji; et al.
Abstract : Aim: Alcoholic hepatocellular carcinoma (ALD‐HCC) accounts for the majority of non‐B non‐C HCC (NBNC‐HCC) cases. Although alcohol is a potent carcinogen, there have been few reports on the influence of modest alcohol consumption in NBNC‐HCC. This study aimed to investigate the clinical characteristics and prognosis of NBNC‐HCC patients with modest alcohol consumption. Methods: From 2007 to 2010, 2283 HCC patients were evaluated at 10 hospitals. We collected detailed etiology data of 588 NBNC‐HCC patients and compared the clinical characteristics and prognosis between ALD‐HCC and modest alcohol‐HCC patients. Results: There were 69 HCC patients with modest alcohol consumption, accounting for 3% of all HCC patients evaluated. This patient group had significantly more women and higher prevalence of Child–Pugh class A, hypertension and advanced disease stage, and were diagnosed with HCC at an older age than the ALD‐HCC group (266 patients). Additionally, among the modest alcohol‐HCC patients, diabetes was significantly more common in the anti‐hepatitis B core (HBc) negative subgroup than in the anti‐HBc positive subgroup. However, no significant difference in survival was observed between the two patient groups regardless of significant differences in tumor staging. Alcohol consumption and metabolic factors were not significant independent predictors of survival. Conclusion: The clinical characteristics of modest alcohol‐HCC included advanced staging, favorable liver reserve capacity and older age at diagnosis. HCC development in patients with modest alcohol consumption may relate to metabolic factors. Although approximately 30% of the evaluated HCC cases were in advanced stages, the prognosis of NBNC‐HCC patients with modest alcohol consumption was relatively favorable.